Immunoglobulin A, G, and M responses to L1 and L2 capsids of human papillomavirus types 6, 11, 16, 18, and 33 L1 after newly acquired infection. Issue 5 (October 1998) - van Doornum, G; Prins, M; Andersson-Ellström, A; Dillner, J
Abstract : OBJECTIVES: We performed a study to establish the pattern of serological reactivity for immunoglobulins (Ig), to capsids of human papilloma virus (HPV) after new HPV infection in two groups of subjects. METHODS: The pattern of serological reactivity after acquisition of infection with HPV was investigated by measuring IgA, IgM, and IgG antibodies to capsids containing L1 and L2 proteins of HPV types 6, 11, 16, 18, and 33 in longitudinal studies of groups with different patterns of sexual activity. Individuals who tested negative for HPV DNA by the polymerase chain reaction at enrolment, but who became HPV DNA positive during follow up, were examined for antibodies to HPV capsids by enzyme linked immunosorbent assay. One group consisted of 15 young girls (with eight controls who remained HPV DNA negative) who were becoming sexually active and the other comprised 12 male (with five controls) and 35 female (with seven controls) heterosexual attenders of a sexually transmitted disease clinic who had had multiple sexual partners. RESULTS: The sexually inexperienced girls showed IgA and IgG responses, but seldom an IgM response to infection with HPV types 6/11, 16, and 18. No consistent pattern of serological reactivity was apparent for the heterosexuals with multiple partners. The lack of association between current HPV DNA positivity and detectable antibodies in these individuals was possibly related to the duration of infection or to prior exposure to HPV. For the latter group serological reactivity to HPV capsids was significantly greater in women than in men (p = 0.001, p = 0.003, and p = 0.024, for IgG to HPV 6, 11, and 16, respectively). CONCLUSION: The sex difference in antibody response detected in previous studies with assays based on peptide antigens was thus corroborated in the present study with capsid based serological assays. This sex difference might reflect a difference in sexual activity and prior exposure to HPV between men and women in this particular group.